Folklore Goes to War: Folksongs, Yangge and Storytelling in Communist Bases during the Second Sino-Japanese War - Selina Gao (IAFOR Journal of Cultural Studies, 2023)
All across the world, folklore studies are often closely tied to the emergence of modern nation states and were used to (re)build national identities. In post-WWI China, a growing community of academics and enthusiastic amateurs began working on folklore projects as part of a larger cultural effort to stoke nationalist sentiment and, by consequence, encourage resistance to foreign encroachment. After Japan’s invasion in the 1930s threw the whole country into crisis, this campaign transformed from the abstract into a strategic component of the Chinese war effort. During China’s War of Resistance against Japan, folklore activities played a valuable role in boosting the national spirit and promoting the idea of China as home to a rich cultural legacy. In communist bases of the North China Plain in particular, a New Literature and Art Movement began with the collection and organization of folk literature and art, which was in turn remoulded into effective and highly politicized anti-Japanese and social reform messages to promote mass mobilization. This article examines folksongs, yangge and storytelling to reveal how folklore, reshaped by communist intellectuals, was designed to serve political aims and address peasants and soldiers in order to unite the masses against its enemies both foreign and demestic. The Chinese Communist Party used traditional forms of folklore with revised content to launch a mass movement that served its primary political needs: winning support of the masses and spreading revolutionary communist ideology to a broader audience. This wartime revolutionary folklore approach continued into peacetime and greatly affected the People’s Republic of China.